Pengaruh Tingkat Pengangguran Terbuka, Rata-Rata Lama Sekolah, dan Usia Harapan Hidup terhadap IPM di Provinsi Jawa Tengah Tahun 2025 - Raina Fatkhi Azkia; Nazilaturrohmah; Dian Isnawati; Aldila Kresnaresanti4 (JURNAL ILMIAH NUSANTARA, 2026)
The Human Development Index (HDI) is an important indicator that measures the quality of life of people in a region. One factor influencing the HDI is the government's ability to improve the quality of life of its people, as measured by average years of schooling, life expectancy, and the open unemployment rate. This study aims to analyze the influence of the Open Unemployment Rate, Average Years of Schooling, and Life Expectancy on the HDI in Central Java Province in 2025. This study uses a quantitative approach with multiple linear regression analysis. The data used are secondary data obtained from the Central Statistics Agency (BPS). The results of the t-test in the study suggest that open unemployment variable has no effect, while the average years of schooling and life expectancy variables have a positive and significant effect on the Human Development Index in Central Java in 2025. Simultaneously, the bopen unemployment, average years of schooling, and life expectancy have a significant effect on the Human Development Index.